A Deluge of Complex Repeats: The Solanum Genome - Mehra, Mrigaya (PLoS One, 2015)
Repetitive elements have lately emerged as key components of genome, performing varieties of roles. It has now become necessary to have an account of repeats for every genome to understand its dynamics and state. Recently, genomes of two major Solanaceae species, Solanum tuberosum and Solanum lycopersicum, were sequenced. These species are important crops having high commercial significance as well as value as model species. However, there is a reasonable gap in information about repetitive elements and their possible roles in genome regulation for these species. The present study was aimed at detailed identification and characterization of complex repetitive elements in these genomes, along with study of their possible functional associations as well as to assess possible transcriptionally active repetitive elements. In this study, it was found that ~50–60% of genomes of S. tuberosum and S. lycopersicum were composed of repetitive elements. It was also found that complex repetitive elements were associated with >95% of genes in both species. These two genomes are mostly composed of LTR retrotransposons. Two novel repeat families very similar to LTR/ERV1 and LINE/RTE-BovB have been reported for the first time. Active existence of complex repeats was estimated by measuring their transcriptional abundance using Next Generation Sequencing read data and Microarray platforms. A reasonable amount of regulatory components like transcription factor binding sites and miRNAs appear to be under the influence of these complex repetitive elements in these species, while several genes appeared to possess exonized repeats.